Celebrities in the heart, strangers in the pancreatic beta cell: Voltage‐gated potassium channels Kv7.1 and Kv11.1 bridge long QT syndrome with hyperinsulinaemia as well as type 2 diabetes. (22nd January 2022) - Lubberding, Anniek F.; Juhl, Christian R.; Skovhøj, Emil Z.; Kanters, Jørgen K.; Mandrup‐Poulsen, Thomas; Torekov, Signe S.
Abstract: Voltage‐gated potassium (Kv ) channels play an important role in the repolarization of a variety of excitable tissues, including in the cardiomyocyte and the pancreatic beta cell. Recently, individuals carrying loss‐of‐function (LoF) mutations in KCNQ1, encoding Kv 7.1, and KCNH2 (hERG), encoding Kv 11.1, were found to exhibit post‐prandial hyperinsulinaemia and episodes of hypoglycaemia. These LoF mutations also cause the cardiac disorder long QT syndrome (LQTS), which can be aggravated by hypoglycaemia. Interestingly, patients with LQTS also have a higher burden of diabetes compared to the background population, an apparent paradox in relation to the hyperinsulinaemic phenotype, and KCNQ1 has been identified as a type 2 diabetes risk gene. This review article summarizes the involvement of delayed rectifier K + channels in pancreatic beta cell function, with emphasis on Kv 7.1 and Kv 11.1, using the cardiomyocyte for context. The functional and clinical consequences of LoF mutations and polymorphisms in these channels on blood glucose homeostasis are explored using evidence from pre‐clinical, clinical and genome‐wide association studies, thereby evaluating the link between LQTS, hyperinsulinaemia and type 2 diabetes.